Mengembangkan Kesenian Tradisional Badui Al-Fattah, Wedomartani, Kabupaten Sleman, DIY: Studi untuk Keberlanjutan Seni Tradisional - Widya Nayati; Hindun Hindun (KALPATARU, 2021)
Since the beginning of 21st century, Bedouin traditional art has declined due to the influence of modern times. It has even shifted to become a tourist attraction. For this reason, efforts are needed to improve human resources for the sustainability of the traditional arts. By using inductive reasoning, this research was conducted to improve the traditional art to be part of Indonesian cultural identity. Direct observations and interviews were made on the traditional Bedouin art group Al Fattah in Wedomartani, Yogyakarta. The outcome of this study is a recommendation for Bedouin art of Al-Fattah to have better management of the accompaniment and sound system, as well as the arrangement of motion gestures so that the art can be more captivating as well as delivering the message to the audience.